1978
DOI: 10.3133/pp1060
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of the Roberts Mountains Allochthon in north-central Nevada

Abstract: During the Antler orogeny in Late Devonian and Early Mississippian time, early and middle Paleozoic siliceous rocks, largely chert and shale, were thrust eastward for 90 to 160 km over coexisting carbonate rocks. Minor and major structures of two small areas of the allochthon at Battle Mountain and in the southern Tuscarora Mountains were studied in order to characterize the deformation and test the consistency of the movement plan with respect to the large eastward displacement. In the Battle Mountain area, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 9 publications
3
19
0
Order By: Relevance
“…However, fold axes in the trend, particularly near mineralized areas, plunge at shallow angles to the NW (Madrid, 1987;Madrid and Bagby, 1986;Volk and Zimmerman, 1991;Peters and Evans, 1995). The NW-trending fold axes were postulated by Evans and Theodore (1978) to be due to Jurassic tectonism, which is compatible with the timing of other tectonic events proposed by Ketner and Smith (1982), Ketner (1987) and Thorman and others (1991b) in northeastern Nevada.…”
Section: Geologic Settingsupporting
confidence: 85%
See 1 more Smart Citation
“…However, fold axes in the trend, particularly near mineralized areas, plunge at shallow angles to the NW (Madrid, 1987;Madrid and Bagby, 1986;Volk and Zimmerman, 1991;Peters and Evans, 1995). The NW-trending fold axes were postulated by Evans and Theodore (1978) to be due to Jurassic tectonism, which is compatible with the timing of other tectonic events proposed by Ketner and Smith (1982), Ketner (1987) and Thorman and others (1991b) in northeastern Nevada.…”
Section: Geologic Settingsupporting
confidence: 85%
“…The gold deposits in the Carlin trend are aligned along a NW-trending belt (Roberts, 1960(Roberts, , 1966Thorman and Christensen, 1991), but definitive geologic parameters have not been shown to account for this alignment. Previous workers in the Carlin trend (Evans and Theodore, 1978) have documented fold axes in the region of the Carlin trend, which plunge at low angles to the NE and SW. This orientation is consistent with orientations documented by Oldow (1984) who noted a relative consistency to deformation symmetry in the Roberts Mountains allochthon and attributed this symmetry to movement and emplacement of the allochthon.…”
Section: Geologic Settingmentioning
confidence: 88%
“…1) comes from regional inspection of fold axes. Evans & Theodore (1978) first demonstrated that the Carlin trend corresponds to a zone of anomalously trending fold axes. Outside the Carlin trend fold axes trend mostly NNE, fairly typical of folds associated with the Antler Orogeny and subsequent compressional events.…”
Section: Northern Carlin Trendmentioning
confidence: 97%
“…The metamorphic grade of RMA rocks is generally greenschist facies or lower (Gehrels, Dickinson, Riley, et al, ). RMA strata are highly deformed and include imbricated older‐over‐younger thrust sheets (e.g., Evans & Theodore, ; Noble & Finney, ; Oldow, ). Together, they have been interpreted as a westward thickening subduction assemblage (e.g., Dickinson, ; Speed & Sleep, ).…”
Section: Mid‐paleozoic Tectonostratigraphic Framework Of Western Laurmentioning
confidence: 99%